O-060 Ethical implications of the direct to consumer genetic testing. What should donors and recipients know?. (6th August 2021) - Frith, L
Abstract: Abstract text The growth in the use of direct-to-consumer-genetic testing (DTCGT) is having a major impact on sperm, egg and embryo donor conception (hereafter donor conception). DTCGT services include family history sites, e.g. Ancestry.com, and medical testing sites, e.g.23andme. Despite the many different motivations people have for using these services, it is now easier to search and find donor relatives, with donor-conceived people, recipients of donor gametes and embryos, and donors all using these services to make hitherto unlikely connections. Some individuals have found large numbers of donor-siblings, while donors have been traced by their adult donor offspring. DTCGT can also reveal unexpected origins with the numbers of people finding out they are donor-conceived through DTCGT rapidly increasing. For example, one woman discovered she was donor conceived after using 23andme to assess her risk of breast cancer, an eventuality she had never anticipated when she decided to take that test. The increasing use of DTCGT has led to claims that donor anonymity is dead and we are entering a new era where the possibilities of finding our genetic relatives and extended family have dramatically expanded. These developments will produce new landscapes where different systems collide and interact, creating new ways of locating and finding donor relatives. In the UK for example, information on genetic relations, donors and donor siblings, is located within two very different systems: 'official' regulatory systems, such as central registers of information held by government bodies such as the Human Fertilisation and Embryology Authority's (HFEA) registers; and emerging digital online systems, of DTCGT. This paper will explore how these new developments interact with existing ways of finding out information about donor relatives and consider the ethical and legal issues and challenges for fertility practice.